Predicting the self-centering behavior of hybrid FRP-steel reinforced concrete beams under blast loading. (15th November 2021) - Johnson, Jalen; Xu, Man; Jacques, Eric
Abstract: An inelastic single-degree-of-freedom (SDOF) dynamic analysis model is developed to predict the entire displacement time-history of concrete beams reinforced with hybrid mixtures of fiber reinforced polymer (FRP) and steel reinforcing bars subjected to blast loads. Hybrid FRP-steel reinforced concrete members exhibit strong self-centering tendencies which promote blast resilience through reductions in residual damage, repair cost, and facility downtime after a terrorist bomb attack or accidental explosion. FRP bars provide an internal restoring force that activates self-centering behavior after the inertial loads are removed, while the conventional steel reinforcement and concrete dissipate energy by their inelastic response. The SDOF model is equally applicable to all-steel, all-FRP, and hybrid FRP-steel reinforced concrete flexural members, incorporating all the relevant parameters of flexural response, nonlinearity, and self-centering that have been observed to play an important role in blast tests. These parameters include the type, size, spacing, arrangement, and material properties of longitudinal and transverse reinforcement, as well as concrete properties and section geometry. The effect of these parameters is described in terms of nonlinear resistance functions capturing the inbound and rebound flexural response, plastic hinge formulations to account for crack bridging provided by FRP bars, and a hysteretic model for the combined effects of self-centering behavior and stiffness degradation due to accumulated damage from progressively increasing repeated blast tests. A new response parameter, known as the Blast Self-Centering Index (BSI), is proposed to evaluate and assess the residual displacements of all-steel, all-FRP, and hybrid FRP-steel reinforced concrete beams predicted by SDOF analysis. The model has been verified extensively against data obtained from explosively driven shock tube blast experiments.